Design of a Light Intensity Regulator with Remote Control for Incandescent Lamps - Januar (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2022)
One of the uses of rice washing water is to make nata de rice or bacterial cellulose. This study was conducted to determine the effect of glucose mass and fermentation time on the viscosity of nata de rice. The study was conducted using 1000 ml of water to wash rice then added 10 ml of acetic acid, glucose with 50 grams, 75 grams and 100 grams, 5 grams urea, Acebacter xylinum starter as much as 100 ml then fermented. up to 14 days. Parameters analyzed were glucose mass and time of optimum fermentation conditions on the thickness of nata de rice. Thickness measurements were carried out using shear anchors. The results showed that the optimum thickness of nata was the addition of 100 grams of glucose with an optimum thickness of 17 mm and the optimum time was on the 14th day during fermentation.